Social capital and digital transformation of startups in Vietnam: the mediating role of access to resources - Tran, Ghi Nha; Nguyen, Dat Hoang Anh; Tran, Khoa Dang; Nguyen, Thach Ha (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this study is to use social capital theory to explain how startups in Vietnam undergo the digital transformation process. The study investigates the connection between social capital, resource access, and digital transformation in Vietnamese startups. 230 managers were analyzed using the Partial Least Squares Structural Model (PLS-SEM). The study found a positive correlation between social capital, resource access, and digital transformation.
Keywords: social capital; access to resources; digital transformation